Segmental Spinal Dysgenesis (Bangladesh Journal of Radiology and Imaging, 2026)
Report on a rare case of segmental spinal dysgenesis of a 07 months old boy. The boy was born with congenital lower limb deformity and focal kyphosis. Radiologycal investigations revealed hypoplasia of vertebral bodies and posterior listhesis leading to focal kyphosis. The aim of reporting this case is to highlight the role of radiological investigations in the diagnosis of extent of spinal abnormalities and provide adequate informations for surgical correction